An Analysis of Financial Ratio Effect with Liquidity and Profitability as Intervening on Sharia Banking Performance in Indonesia for the Years 2015-2018 - Anton Bawono; Faisal Falakh (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2019)
The paper aims to measure the effect of CAR, NPF, OER, FDR and NOM toward profitability discribed by Return on Assets ratio of sharia banking performance in Indonesia with FDR and NOM as intervening variable. This research uses quantitative method with multiple regression analysis. The samples have taken from sharia banking monthly report that published by Otoritas Jasa Keuangan for the years of 2015 until 2018 in the last month of the issued report. It has analyzed by using an analysis tool, Eviews 9. The results showed that efficiency ratio has negative impact toward ROA. Otherwise, CAR, NPF, FDR and NOM have no significant effect. For the path analysis, FDR and NOM cannot mediating the effect of financial ratio toward ROA.